Community health worker and caregiver experiences and perceptions of a multimodal handheld pulse oximeter used in sick child consultations in rural Burundi: A qualitative evaluation. - Sarah Bauler; Leocadie Nivyindika; Titus Kirwa; Vital Habonimana; Dionis Nizigiyimana; Miles A Kirby; Asrat Tolossa (PLOS Global Public Health)
Community Health Workers (CHWs) in low- and middle-income countries are essential in providing primary health care to remote communities. However, due to limited diagnostic tools, CHWs often struggle to correctly identify childhood illnesses, especially pneumonia. We conducted a prospective pilot study and used qualitative research methods to evaluate acceptability and feasibility of a multimodal pulse oximeter used by CHWs during their integrated community case management (iCCM) of childhood illness consultations in rural Burundi. We used purposive sampling to recruit CHWs and trained them to use the oximeters during household iCCM consultations for children 6-59 months of age. After eight weeks of using the devices, we conducted eight focus group discussions to evaluate experiences and perceptions of the device among CHWs and caregivers. Our thematic analysis, based upon deductive and inductive reasoning, identified the following themes: durability, storability, trust, self-efficacy, child agitation, ease of using the device, and interpretation of parameters. CHWs deemed the devices highly acceptable and took pride in safely storing them but reported challenges in utilizing respiration rate, pulse, and oxygen saturation (though temperature was understood). Child agitation was a barrier to oximeter use, especially among children 6-12 months. Additional CHW capacity-building on interpreting parameters is needed when using oximeters during household iCCM consultations in Burundi, including an iCCM job aid (decision-making tree) with oxygen saturation and respiratory rate cut-offs for treatment and/or referral. Training and using child-calming techniques could be an important strategy for obtaining quality measurements. While CHWs and caregivers highly valued the oximeters during sick child visits, the devices may be better utilized and scalable at the health facility level.